Costs and consequences of the Portuguese needle-exchange program in community pharmacies. (May 2020) - Borges, Margarida; Gouveia, Miguel; Fiorentino, Francesca; Jesus, Gonçalo; Cary, Maria; Guerreiro, José Pedro; Costa, Suzete; Carneiro, António Vaz
Background: Needle-exchange programs (NEPs) reduce infections in people who inject drugs. This study assesses the impact community pharmacies have had in the Needle-Exchange Program in Portugal since 2015. Methods: Health gains were measured by the number of human immunodeficiency virus (HIV) and hepatitis C virus (HCV) infections averted, which were estimated, in each scenario, based on a standard model in the literature, calibrated to national data. The costs per infection were taken from national literature; costs of manufacturing, logistics and incineration of injection materials were also considered. The results were presented as net costs (i.e., incremental costs of the program with community pharmacies less the costs of additional infections avoided). Results: Considering a 5-year horizon, the Needle Exchange Program with community pharmacies would account for a 6.8% ( n = 25) and a 6.5% reduction ( n = 22) of HCV and HIV infections, respectively. The present value of net savings generated by the participation of community pharmacies in the program was estimated at €2, 073, 347. The average discounted net benefit per syringe exchanged is €3.01, already taking into account a payment to community pharmacies per needle exchanged. Interpretation: We estimate that the participation of community pharmacies in the Needle Exchange Program will lead to a reduction of HIV and HCV infections and will generate over €2 million in savings for the health system. Conclusions: The intervention is estimated to generate better health outcomes at lower costs, contributing to improving the efficiency of the public health system in Portugal.